Time Delay Risk Analysis in SMPN 2 Mantup Classroom Construction: Analisis Risiko Penundaan Waktu dalam Konstruksi Ruang Kelas SMPN 2 Mantup - Prambudi, Wahyu Tri; N. Riwibowo; Cahyaningrum, Fibia Sentauri; Ariyanti, Menik; Rizki, M. Alvan (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Timely completion of construction projects is critical for operational efficiency and cost management. Specific Background: The New Classroom Building Project at SMPN 2 Mantup-Lamongan experienced delays caused by human resources, material availability, and weather conditions, highlighting challenges in project scheduling and risk management. Knowledge Gap: Limited studies provide quantitative assessments of combined environmental, material, and workforce factors on construction delays in local school infrastructure projects. Aims: This study aims to analyze the magnitude of time delays, identify dominant risk factors, and propose mitigation strategies to manage project risks effectively. Results: Data from 45 respondents using questionnaires and analyzed via SPSS revealed that rainfall intensity (21.6%), workforce skill (16.8%), and worker discipline (14.4%) were the leading contributors to delays, with an overall project delay of 6 days compared to the planned schedule. Novelty: The research integrates Critical Path Method calculations with survey-based risk assessment to provide a precise, practical strategy for local construction projects. Implications: Findings offer actionable guidance for contractors and project managers to optimize resource allocation, reduce delays, and improve project reliability. Highlights: Rainfall intensity identified as the highest delay factor. Workforce skill and discipline significantly affect project duration. CPM combined with survey analysis provides actionable mitigation strategies. Keywords: Construction Delays, Risk Analysis, Critical Path, Project Management, SMPN 2 Mantup